Even the Darkest Stars : Even The Darkest Stars # 1 - Fawcett, Heather (New York : Balzer + Bray, an imprint of HarperCollinsPublishers, 2017)
When River Shara, a great explorer, arrives in her village looking to hire Kamzin for his next expedition, she finds herself racing her sister and a rival explorer up the tallest and deadliest mountain in the Aryas.
Keywords: Fantasy; Sisters -- Fiction; Mountaineering -- Fiction; Survival -- Fiction